Acordo de não persecução penal: instrumento de concretização do processo penal resolutivo e eficiente - Araujo, Juliana Moyzés Nepomuceno (2021)
Due to the scenario in which the Criminal Justice is characterized by its inefficiency and slowness, by crimes' sophistication and the sensation of impunity that has been disseminated throughout the society, the debate on criminal procedure science's efficiency and on the need to apply Consensual Justice to address society's demands on the post-modernity is imperative. In this regard, the concepts and the premises from the Law and Economics directly influenced the adoption of consensus at criminal prosecution, based on an economic approach that has the purpose to attain an effective procedure and to maximize the efficiency based on the cost-benefit analysis of the criminal offense perpetrated. The Consensual Criminal Justice is justified by the need of a contemporary criminal process that should not use obsolete and inefficient resources to effectively fight crime, so that consensual tools emerge as a modern method to obtain effective solutions, characterizing itself for the celerity, efficiency and observance of the parties' rights and guarantees, also allowing the recovery of the victim's importance in the persecutory activity. Thus, the scope of this work is to analyze the political-criminal genesis and the important aspects of the non-criminal prosecution agreement, that is part of the Consensual Criminal Justice and was introduced by the Criminal Procedure Code with the enactment of the Law n. 13,964/2019, aiming to demonstrate its role as a primary criminal policy instrument in the development of a resolute and efficient criminal process. The research, based on the deductive method, was carried out using a qualitative methodology, drawing on doctrines, articles, legislation and jurisprudence. It proposes to demonstrate the importance of employing methods that help implement a more rational criminal science, which is urgent and necessary to change the scenario in which Criminal Justice is presented. It is inferred, therefore, that the non-criminal prosecution agreement, as an adequate and efficient consensual technique to the current social reality, plays a fundamental role in the resumption of the prestige and confidence in the achievement of Justice